2020
DOI: 10.1186/s10194-020-01107-4
|View full text |Cite
|
Sign up to set email alerts
|

Lost productivity associated with headache and depression: a quality improvement project identifying a patient population at risk

Abstract: Objective: This quality improvement project was implemented in order to highlight the association between headache, mTBI and depression on lost productivity and resource utilization. Background: Mood disorders, environment and traumatic brain injury are common in patients with headache, and have been shown to influence clinical course, treatment response and outcome. Although widely recognized, the association of these factors on clinical outcomes, resource utilization and productivity is not well understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Another US study discovered that depression was highly correlated with productivity loss in the headache population, and thus concluded that early recognition and treatment of comorbid depression could improve QoL and productivity as well as decrease healthcare resource use [46]. It highlighted the importance to understand the common comorbidities of migraine in Japan that is currently lacking, and how controlling these comorbidities might help to improve the overall health outcomes of patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Another US study discovered that depression was highly correlated with productivity loss in the headache population, and thus concluded that early recognition and treatment of comorbid depression could improve QoL and productivity as well as decrease healthcare resource use [46]. It highlighted the importance to understand the common comorbidities of migraine in Japan that is currently lacking, and how controlling these comorbidities might help to improve the overall health outcomes of patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, non-pharmacological approaches, such as nutraceuticals, non-invasive neurostimulation, behavioral therapies and physical therapy, represent valid complementary options especially for patients with specific comorbidities, for those overusing medication, or for pregnant women [14][15][16][17]. A major awareness of the role of comorbidity in primary headache may therefore help clinicians in clinical management, improve headache sufferers' quality of life and reduce impact on societies, defined in terms of disability, cost or reduced work productivity [4,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Mild TBI (mTBI) is the leading cause of death and disabilities in the United States and worldwide, with approximately 42 million cases annually [ 3 ]. Patients may present a complex array of symptoms, including cognitive disturbance, physical fatigue, decreased sleep quality [ 4 ], and depression or migraine [ 5 ]. Further insights into the underlying biological injury should be obtained, and the identification of key genes is essential for finding biomarkers and therapeutic targets for the mTBI.…”
Section: Introductionmentioning
confidence: 99%